A case of ceftriaxone-associated biliary pseudolithiasis in an elderly patient with renal dysfunction. (2017) - Abe, Shuichi
Abstract: Prior literature suggests that ceftriaxone causes formation of gallbladder stones at a relatively high frequency, and when abdominal symptoms occur, prompt investigation of the gallbladder is required with institution of appropriate treatment. Aging, malnutrition, renal impairment, and sepsis are risk factors for pseudolithiasis, and prevention of these is important to suppress gallstone development.